The HDAC Inhibitor Phenylbutyrate Reverses Effects of Neonatal Ventral Hippocampal Lesion in Rats - Sandner, Guy; Host, Lionel; Angst, Marie-Josée; Guiberteau, Thierry; Guignard, Blandine; Zwiller, Jean (Frontiers in Psychiatry, 2011)
Recent evidence suggests that epigenetic mechanisms play a role in psychiatric diseases. In this study, we considered rats with neonatal ventral hippocampal lesions (NVHL) that are currently used for modeling neurodevelopmental aspects of schizophrenia. Contribution of epigenetic regulation to the effects of the lesion was investigated, using a histone deacetylase (HDAC) inhibitor. Lesioned or sham-operated rats were treated with the general HDAC inhibitor phenylbutyrate, which was injected daily from the day after surgery until adulthood. Changes in the volume of the lesion were monitored by magnetic resonance imaging (MRI). Anxiety was analyzed in the Plus Maze Test. Hypersensitivity of the dopaminergic system was evaluated by measuring the locomotor response to apomorphine. An associative conditioning test rewarded with food was used to evaluate learning abilities. The volume of the lesions expanded long after surgery, independently of the treatment, as assessed by MRI. Removal of the ventral hippocampus reduced anxiety, and this remained unchanged when animals were treated with phenylbutyrate. In contrast, NVHL rats’ hypersensitivity to apomorphine and deterioration of the associative learning were reduced by the treatment. Global HDAC activity, which was increased in the prefrontal cortex of lesioned non-treated rats, was found to be reversed by HDAC inhibition. The study provides evidence that chromatin remodeling may be useful for limiting behavioral consequences due to lesioning of the ventral hippocampus at an early age. This represents a novel approach for treating disorders resulting from insults occurring during brain development.